Deskripsi Pelaksanaan Program Intervensi Dini pada Pemerolehan Bahasa Pertama Anak Down Syndrome melalui Penerapan Konsep Family Quality of Life - Rahmi Khalida; Ulfa Suryani (Jurnal Ilmu Keperawatan Jiwa, 2021)
One type of child with special needs is Down Syndrome. His existence will affect the family with its limitations. The title of this study is "Description of The Implementation of Early Intervention Program in The Acquisition of The First Language of Down Syndrome Children Through the Application of The Concept of Family Quality Of Life". The purpose of the study was to describe the implementation of early intervention in the acquisition of the first language of Down Syndrome children. The research method is qualitative with qualitative descriptive approach. The data is obtained by interview and observation methods. The study subjects were families with down syndrome children. Data processing is done by means of content analysis. The results showed that (1) early intervention programs through the application of the concept of family quality of life can help parents of down syndrome children overcome problems in the acquisition of first language (2) FQoL dimensions in the family can realize the quality of life of the family, especially children (3) the need for expert cooperation in the field of services for children with special needs to improve the knowledge and understanding of parents in providing early intervention in children with special needs.